Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-82550-4
|View full text |Cite
|
Sign up to set email alerts
|

New combination approaches to combat methicillin-resistant Staphylococcus aureus (MRSA)

Abstract: The herbal products proved to be more promising antimicrobials even though their antimicrobial activity is milder than commercially available antibiotics. Moreover, herbal drugs may act synergistically with antibiotics to kill microbes. In this study, we aimed to enhance the activity of penicillin against MRSA through combination with the active saponin fraction isolated from the Zygophyllum album plant. Three different types of metabolites (saponins, sterols, and phenolics) have been extracted from Zygophyllu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 39 publications
1
41
1
Order By: Relevance
“…e cytotoxic activity of the isolated compounds was determined using the brine shrimp (Artemia salina) lethality test. e results showed that, among the isolated compounds, grindelic acid (1) and penduletin (5) were able to inhibit the crustaceans in all tested concentrations (10.0, 5.0, and 1.0 mg ml −1 ) while grindelic acid (1) had the highest activity comparing with other isolated compounds. e average activity was showed by retusine (2) and 5, 7, 3′-trihydroxy-3, 4′-dimethoxyflavone (7); these compounds were active at 10-5 mg ml −1 and inactive at 1 mg ml −1 .…”
Section: Cytotoxic Activitymentioning
confidence: 91%
See 2 more Smart Citations
“…e cytotoxic activity of the isolated compounds was determined using the brine shrimp (Artemia salina) lethality test. e results showed that, among the isolated compounds, grindelic acid (1) and penduletin (5) were able to inhibit the crustaceans in all tested concentrations (10.0, 5.0, and 1.0 mg ml −1 ) while grindelic acid (1) had the highest activity comparing with other isolated compounds. e average activity was showed by retusine (2) and 5, 7, 3′-trihydroxy-3, 4′-dimethoxyflavone (7); these compounds were active at 10-5 mg ml −1 and inactive at 1 mg ml −1 .…”
Section: Cytotoxic Activitymentioning
confidence: 91%
“…e global increase in antibiotic resistance causes an increase in medical costs and mortality rates, especially with some severe bacterial infections such as pneumonia, tuberculosis, gonorrhea, and salmonellosis [4]. Natural products can be considered as the main source of antimicrobial and anticancer compounds [5]. e activity of natural products either originated from plants [5][6][7], marines [8,9] or fungi [10][11][12][13][14] is owned to a diversity of secondary metabolites that belong to various chemical classes such as flavonoids [15][16][17], saponins [6,18], pyrones [19], isochromenes [20], and alkaloids [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural secondary metabolites are a significant source for anti-infective agents since dawn of history. ese metabolites are found in many sources in nature such as plants [14,15], marines [16,17], and microbes [18][19][20], and they could be assorted following their chemical structure into countless classes such as saponins [21,22], diterpenes [23], pyrones [24], isochromenes [25], flavonoids [26,27], and alkaloids [28].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are the key source that humankind relied on to treat diseases and maintain good health [1,2]. e effective secondary metabolites that are responsible for natural products' activity could be derived from plants [3,4] or marines [5,6]. Furthermore, fungi represent an unlimited origin of bioactive metabolites [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%